PRIMARY SCHOOL TEACHERS’ APPROACH TO ADVANTAGES OF ICT USE IN EDUCATION - Braslauskienė, Rasa; Šmitienė, Gražina; Vismantienė, Reda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article reveals primary school teachers’ approach towards advantages and disadvantages of information and communication technologies, their influence to children education as well as teacher experience in the application of ICT technologies in primary education and opportunities of teachers in the development of professional competence. Qualitative study (structured interview) was carried out which involved the teachers of 1 – 4 forms more than four years actively using ICT in the classroom. According to the teachers, Content analysis of the study results revealed essential  factors and potential ways of more efficient use of ICT in primary education, i. e .improvement of teachers’ special professional competence (knowledge, skills and ability to use various ICT tools in the classroom, identification of special needs of primary school children, linking the development of formal and informal needs, etc.), personal viewpoint to ICT in social life, the shortage of ICT tools in primary school.